PENYELESAIAN TINDAK PIDANA PENGANIAYAAN MELALUI HUKUM ADAT DI KECAMATAN PUJUD - Arifin, Muhammad; ', Firdaus; ', Erdianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
In the Indonesian positive law, criminal matters must be resolved in the process of court. But in certain cases it is possible their settlement out of court, one of which is the completion undertaken by traditional institutions, namely through the intermediary Ninik Mamak, as an alternative to settling disputes in the field of criminal law in the application of customary law, such as those in Sub Pujud. Research aims: First, determine and analyze the completion of the crime of persecution under customary law; Second, know and analyze the dispute in the completion of the crime of persecution and Third, find out and analyze the efforts and roles performed by Ninik Mamak customary in tackling crime.This type of research is yuridissosiologis, conducted in Kecamatan Pujud, Rokan Hilir. Population and samples are overall the parties relating to the issues qualitative. Embassy story used is primary story, secondary data and data tertiary denganTeknik collecting story through interviews, questionnaires and studies literature. From the research, there are three finally. One more, In the resolution of criminal acts of persecution still adheres to the settlement that is familial with deliberation in reaching a decision based on the provisions of indigenous done Ninik Mamak. Two intermediaries, dispute settlement constraints persecution crime is the lack of understanding of the community indigenous to the completion of the follow penal . There, efforts made to overcome the criminal act is to disseminate by Ninik Mamak indigenous to the nephew respectively of preventing abuse from becoming simple. Autinetion Author, First, is recommended to conduct a study and explore the local wisdom adat and a number of laws related to the existence and authority of traditional institutions in resolving a case that recognized indigenous and authority in resolving a problem law. Two, Ninik Mamak order custom enhanced its ability to protect children. There,completion deed penal persecution must be maintained in every issue which occurred in the middle of the community as a form of respect and uphold the customs as the main protection. Keywords: Completion-criminal Act –Law Adat